The Human Ecology of Wetlands in Least Developed Countries in Time of Climate Change: Policy and Strategy Implications for Wise Use and Conservation of Wetlands - Ogato, Gemechu Shale (American Journal of Human Ecology, 2013)
<!--[if gte mso 9]> <![endif]--> This article is an outcome of the desk study on “The Human Ecology of Wetlands in Least Developed Countries (LDCs) in Time of Climate Chang: Policy Implications for Wise Use and Conservation of Wetlands.” Wetlands are among the most important ecosystems on Earth because of their unique hydrologic conditions and their role as ecotones between terrestrial and aquatic systems. Although many uses and values of wetlands are evident, historically wetlands have been regarded as wastelands which if possible, should be turned into something else that would be more useful. As a result, wetlands have been drained, turned into agricultural land, and commercial and residential developments at an alarming rate. The general objective of the study is to evaluate the status of wetlands in LDCs in time of climate change and identify policy and strategy implications. The findings of the study confirm that mainstreaming climate change adaptation and mitigation into sustainable development and natural resources conservation efforts of least developed countries (LDCs) is of paramount importance for conservation and sustainable utilization of wetlands in time of climate change. In conclusion, this review confirmed that deep wetlands generally capture carbon dioxide from and release methane to the atmosphere and the combination of these two fluxes determines whether these countervailing processes make a wetland system an overall contributor to the greenhouse effect. Moreover, both natural processes and human activities are responsible for the predicted wetland losses in least developed countries. Least Developed Countries may benefit from sustainable utilization and conservation of wetlands by responding to implications like anticipatory and systematic ‘Climate Change integrated Conservation Strategies’ in time of climate change. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->